2018
DOI: 10.3892/ol.2018.9616
|View full text |Cite
|
Sign up to set email alerts
|

Rotundic acid induces Cas3‑MCF‑7 cell apoptosis through the p53 pathway

Abstract: In the present study, the functions and mechanisms of rotundic acid (RA) underlying its induction of apoptosis in caspase-3-transfected MCF-7 human breast cancer cells (Cas3-MCF-7 cells) were investigated. RA induced apoptosis in Cas3-MCF-7 cells more efficiently compared with that in MCF-7 cells transfected with control plasmid. The results from an MTT assay demonstrated that RA effectively inhibited Cas3-MCF-7 cell viability in a dose-dependent manner and induced cell apoptosis via caspase-3 activity within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Another experimental result also found that the MCF7 cells are caspase-3 deficient with a partial deletion in the CASP-3 gene; these cells underwent cell death that lacked typical apoptotic properties 53 . However, Nan et al confirmed that caspase-3 serves a critical function in MCF7 cell, and they suggested that caspase-3 deficiency may contribute to the chemotherapy-resistance of breast cancer 38 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Another experimental result also found that the MCF7 cells are caspase-3 deficient with a partial deletion in the CASP-3 gene; these cells underwent cell death that lacked typical apoptotic properties 53 . However, Nan et al confirmed that caspase-3 serves a critical function in MCF7 cell, and they suggested that caspase-3 deficiency may contribute to the chemotherapy-resistance of breast cancer 38 , 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Rotundic acid (RA), a plant-derived and ursane-type pentacyclic triterpene acid, was identified as a major active ingredient of IRC and has been shown to exert extensive pharmacological effects, including antimicrobial [ 3 , 4 ], anti-inflammatory [ 5 ], anticancer [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ], and lipid-decreasing effects [ 14 ]. It has also been proven to alleviate type 2 diabetes and its complications by improving the composition of the gut microbiota [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rotundic acid (RA) belongs to the pentacyclic triterpenoid family and is mainly found in water fly thrips such as Ilex rotundus, which are widely distributed in China Haraguchiet & Xie et al [17,18]. Previous studies reported the anticancer efficacy of RA both in vitro and in vivo Nan & Roy et al [19,20]. However, the effects of RA in treating IHD remain enigmatic.…”
mentioning
confidence: 99%